2021
DOI: 10.1021/acs.jafc.1c03519
|View full text |Cite
|
Sign up to set email alerts
|

Structural Characterization of Lignin-Carbohydrate Complexes (LCCs) and Their Biotransformation by Intestinal Microbiota In Vitro

Abstract: Lignin-carbohydrate complexes (LCCs) have recently emerged as natural products with pharmaceutical and nutraceutical potential. Here, we compared the structure of LCCs from ginkgo (GK, gymnosperms), wheat straw (WST, monocotyledons), and aspen white poplar (AW, dicotyledons). We also investigated the biotransformation of LCCs by intestinal microbiota in vitro. We found that human intestinal microbiota could use LCCs as a carbon source for growth, breaking resistant cross-linkages in LCCs to generate a plethora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Propionic acid can improve insulin sensitivity and lowers hepatic and plasma concentrations of fatty acids, and this therefore might prove to be an elusive effector of obesity and type II diabetes [ 34 ]. Zhang et al reported that LCC from different plants could be used as substrate for in vitro fermentation to increase the production of SCFAs [ 17 ]. This agrees with the results of the current study with BW-LCC as substrate.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Propionic acid can improve insulin sensitivity and lowers hepatic and plasma concentrations of fatty acids, and this therefore might prove to be an elusive effector of obesity and type II diabetes [ 34 ]. Zhang et al reported that LCC from different plants could be used as substrate for in vitro fermentation to increase the production of SCFAs [ 17 ]. This agrees with the results of the current study with BW-LCC as substrate.…”
Section: Resultsmentioning
confidence: 99%
“…In vitro studies revealed that lignin was an obstacle, as high-lignin content was more slowly digested by gut microbiota compared to low-lignin content [ 16 ]. Currently, in vitro fermentation of LCC from different plant sources has revealed that LCC could be utilized as a substrate to generate SCFAs and aromatic compounds and increase the growth rate of gut microbiota [ 17 ]. As of yet, it is not clear what effect LCC has on the composition of microbiota in the human gut.…”
Section: Introductionmentioning
confidence: 99%
“…The supernatant was withdrawn periodically and used for the measurement of the concentration of total phenol and reducing sugar. The determination of total phenol and reducing sugar were conducted as previously described ( Yu et al, 2009 ; Zhang et al, 2021 ). Qualitative analysis of the depolymerized monomers in the supernatant was performed based on the GC/MS analysis described above.…”
Section: Methodsmentioning
confidence: 99%
“…16 In a human study, lignin was found to be undigested in both the small and large bowel 17 though, conversely, there is also evidence that lignin can be fermented by the intestinal microbiome to smaller molecular weight compounds in the large bowel. 18,19 Whether these lignin-derived metabolites or degradation components retain any iron chelating properties remains undetermined.…”
Section: Introductionmentioning
confidence: 99%